Carbon disulfide reagent allows the characterization of nonpolar analytes by atmospheric pressure chemical ionization mass spectrometry - Owen, Benjamin C.; Gao, Jinshan; Borton, David J.; Amundson, Lucas M.; Archibold, Enada F.; Tan, Xiaoli; Azyat, Khalid; Tykwinski, Rik; Gray, Murray; Kenttaemaa, Hilkka I. (Rapid Communications in Mass Spectrometry, 2011)
While atmospheric pressure ionization methodologies have revolutionized the mass spectrometric analysis of nonvolatile analytes, limitations native to the chemistry of these methodologies hinder or entirely inhibit the analysis of certain analytes, specifically, many nonpolar compounds. Examination of various analytes, including asphaltene and lignin model compounds as well as saturated hydrocarbons, demonstrates that atmospheric pressure chemical ionization (APCI) using CS as the reagent produces an abundant and stable molecular ion (M ) for all model compounds studied, with the exception of completely saturated aliphatic hydrocarbons and the two amino acids tested, arginine and phenylalanine. This reagent substantially broadens the applicability of mass spectrometry to nonvolatile nonpolar analytes and also facilitates the examination of radical cation chemistry by mass spectrometry. Copyright © 2011 John Wiley & Sons, Ltd.